Efektivitas Pengembalian Dana Pinjaman Kelompok Simpan Pinjam Perempuan (SPP) PNPM Mandiri Perdesaan - Mahmud, Mahmud; Nuddin, Andi; Sitti Halimah, Andi (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
Women's Savings and Loans (SPP) is a PNPM-MP program that provides capital to women's groups in the form of savings and loan funds for those who already have a business. In general, the activity aims to develop the potential of rural savings and loan activities, the ease of access to micro-scale business funding, the fulfillment of basic social funding needs, strengthen institutional activities for women, and encourage the prevention of poor households (RTM). The study aims to analyze the effectiveness of loan repayments and describe the obstacles for group members in repaying the loan funds. By the simple analysis, the data obtained from the questionnaire will be tabulated to determine the rate of return on revolving fund loans in the SPP program. The primary and secondary data obtained will be analyzed with a qualitative descriptive analysis by comparing conditions in the field with targets, indicators, and other measures set by PNPM Mandiri in Rural Areas. The study results showed that the effectiveness of loan repayments for the women-only savings and loans group decreased due to the increase in collectibility. On the other hand, the obstacles of repaying loan funds include the number of funds not adjusted to the scale of the business, not having a sense of responsibility in the use and repayment of loan funds, weak knowledge of entrepreneurship, and the inoperability of the joint responsibility system in groups.